Pemberdayaan Masyarakat Melalui Sosialisasi Pemanduan Wisata di Desa Ekowisata Pancoh - Marshanda, Kurnia; Amelia, Viona (CV. Kurnia Grup, 2024)
Rural areas as the locus of tourism development need to prepare themselves to welcome the arrival of tourists. In order to create an empowered village community, one of the initial strategies that can be implemented is through a community service programme through socialisation of community empowerment through tour guiding in Pancoh Ecotourism Village. The socialisation of tour guiding activities is delivered through lecture and discussion methods about tour guiding, what things the guide needs to prepare before meeting tourists, and ways to find out the type or characteristics of tourists. Through this community service programme, the capacity of local human resources is prepared as well as possible to receive tourist visits and be able to provide services and guides according to professional standards. This community service programme is held to create a learning space for the community to improve their knowledge and abilities in the field of tour guiding.